Education and development of Geography teachers´ professionalism (Olhar de Professor, 2011)
This article discusses the process of appropriation, production and development of the required knowledge for the teaching of Geography. It is based on research about teachers´ professionalization and its main issue, which is, teaching knowledge. The article intends to contribute to the acknowledgment and valuing of the teaching profession and, in particular, to the improvement of the processes of Geography teachers´ education. In addition to the literature review, information and data were obtained from classroom observations and interviews with five experienced and qualified Geography teachers in Maringá, PR. It was observed that in general Geography teachers have a view of their work and profession common to the professionals of the area. Teachers notice that the geographical discourse, its themes, concepts and procedures are important for the strengthening not only of the identity of the discipline, but also of their own professionalization. Teachers define themselves as teachers in a broad way, but try to be acknowledged as Geography teachers. By doing this, they take as a framework a specific traditional school Geography, which based on the historical development of the referred science and by the produced and accumulated knowledge through their professional experience is evaluated and continuously recreated.
Keywords: Geography teacher education. Teaching knowledge. Professionalism. Geography Teaching.